Does Tagging and Handling Affect the Growth of Northern Fur Seal Pups ( Callorhinus ursinus )? - Trites, Andrew W. (Canadian Journal of Fisheries and Aquatic Sciences, 1991)
From 1957 to 1966, samples of tagged and marked northern fur seal pups (Callorhinus ursinus) consistently weighed less than untagged and unmarked pups on the Pribilof Islands, Alaska. At the time, it was concluded that tagging and handling had caused a loss of weight and had slowed the normal rate of pup growth. In re-evaluating the data from this time period, it seems that tagged pups grew at the same rate as untagged pups, but were smaller at the time of tagging than average size pups. The growth curve for tagged pups appears to lag behind that of untagged pups, suggesting that tagged pups were born later in the breeding season and were more susceptible to being captured and tagged than older and heavier pups.